Phase-synchronous detection of coherent and incoherent nonlinear signals. (20th November 2015) - Karki, Khadga Jung; Kringle, Loni; Marcus, Andrew H; Pullerits, Tõnu
Abstract: The nonlinear optical response of a material system contains detailed information about its electronic structure. Standard approaches to nonlinear spectroscopy often use multiple beams crossed in a sample, and detect the wave vector matched polarization in transmission. Here, we apply a phase-synchronous digital detection scheme using an excitation geometry with two phase-modulated collinear ultrafast pulses. This scheme can be used to efficiently detect nonlinear coherent signals and incoherent signals, such as higher harmonics and multiphoton fluorescence and photocurrent, from various systems including a photocell device. We present theory and experiment to demonstrate that when the phase of each laser pulse is modulated at the frequency and respectively, nonlinear signals can be isolated at the frequencies where This approach holds promise for performing nonlinear spectroscopic measurements under low-signal conditions.